Inti College Malaysia's Foray Into The International Higher Education Scene: An Analysis Of The International Marketing Strategies Of Inti College Malaysia - Foon, Lee Li (2002)
The international marketing of INTI will be studied to assess its foray into the international scene of higher learning, to determine INTI's strengths in its marketing activities and to forecast the possible obstacles and catalysts that this private Malaysian college will face, and to suggest its possible solutions. This case will also look into its foray into the international education market and how a small time college would be able to ally with overseas universities to provide quality education, resulting in the establishment of branches outside of Malaysia. This case highlights the international marketing of INTI College and the author will suggest possible enhancements of the international marketing strategies as employed by the college. The author will gauge the analysis of the international marketing of INTI College Malaysia through hands-on data gathering, which the author procured as long as the duration the author worked in the college and through literature review.